Building A Website Integrated With Ai Chatbot For Booking Medical Appointment And Health Consultation - Nguyen, Dinh Tai (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Software Engineering; 2020 - 2025